Temporal analysis of prostaglandin F2 alpha receptor, caspase 3, and cyclooxygenase 2 messenger RNA expression and prostaglandin F2 alpha receptor and cyclooxygenase 2 protein expression in endometrial tissue from multiparous Nelore (Bos taurus indicus) cows treated with cloprostenol sodium during puerperium - Moraes, Carolina N. de [UNESP]; Maia, Leandro [UNESP]; Lima, Paula F. de [UNESP]; Dias, Marianne C. [UNESP]; Raposo-Ferreira, Talita M. M. [UNESP]; Sudano, Mateus J.; Buratini Junior, José [UNESP]; Oba, Eunice [UNESP] (Elsevier B.V., 2015)
The use of cloprostenol sodium in puerperium is questionable, as both favorable and unfavorable responses during the uterine involution process have been reported in the literature. This study is based on the hypothesis that cloprostenol sodium promotes modifications in the prostaglandin F2 alpha receptor (FP), caspase 3 (CASP-3), and cyclooxygenase 2 (COX-2) mRNA expression that may favor the process of postpartum uterine involution in multiparous Nelore (Bos taurus indicus) females. Additionally, we aimed to describe the presence and immunolocalization of the FP and COX-2 protein in endometrial tissue at different postpartum time points in these females. Multiparous Nelore cows (n = 24) were treated with cloprostenol sodium (n = 12) or saline solution (n = 12) on postpartum Days 1 and 4 (Day 0 = birth), and endometrial biopsies were performed with a Yomann biopsy instrument and collected on Days I, 7, 14, 28, and 42 postpartum. The mRNA expression from samples on the Days 1, 7,14, 28, and 42 and the protein expression from samples on the Days 1, 14, 28, and 42 were then analyzed. The treated cows had altered FP and CASP-3 mRNA expression, and FP and COX-2 protein were observed in the endometrial surface epithelium, the stroma, and the glandular epithelium, with cytoplasmic immunolocalization. Although we attribute the change in CASP-3 mRNA expression to physiological phenomena, the results obtained for FP mRNA expression opens new doors for the study of hormonal protocols associated with cloprostenol sodium in the puerperium of Zebu females. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Bovine; Cloprostenol sodium; Immunohistochemistry; Puerperium; Prostaglandin F2 alpha receptor